Business analysis - Paul, Debra; Cadle, James; Yeates, Donald (BCS Learning & Development Limited, 2014)
Business analysts must respond to the challenges of today's highly competitive global economy by developing practical, creative and financially sound solutions that will address business problems and grasp new opportunities. This excellent guide sets out the essential toolkit required. It is also ideal for students wanting to gain university and industry qualifications in business analysis and information systems, and is particularly beneficial for those studying for the BCS Professional Certificate in Business Analysis. Important additions in the third edition include expanded discussions regarding gap analysis and benefits management, the impact of Agile software development and an introduction to business architecture.
Keywords: Management information systems.; System analysis.; Organizational effectiveness.; Business planning.; Business analysts.; Strategic planning.; elektronické knihy; electronic books